2017
DOI: 10.5812/jhealthscope.62592
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Education Based on Health Promotion Model (HPM) on Adherence to Antiretroviral Therapy (ART) in HIV- Infected Patients

Abstract: Background: For efficient HIV treatment, it is necessary to follow a precise therapeutic plan. Thus, the present study aimed at using the health promotion model (HPM), which is in adherence to Antiretroviral Therapy (ART), as a theoretical framework to design an educational plan for HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…Social support from family and friends through motivation and encouragement plays a major role in ensuring that people living with HIV remains in care, as they become their primary source of support. In this study, the participants indicated that their family members and friends encouraged them, which was also found in Noroozi et al ( 2017 :7). Their family and friends were able to give health advice where they could, which indicates the importance of involving the family in the care of people living with HIV by educating them when they accompany their loved ones for clinic visits (Pius et al 2021 :6).…”
Section: Discussionsupporting
confidence: 85%
“…Social support from family and friends through motivation and encouragement plays a major role in ensuring that people living with HIV remains in care, as they become their primary source of support. In this study, the participants indicated that their family members and friends encouraged them, which was also found in Noroozi et al ( 2017 :7). Their family and friends were able to give health advice where they could, which indicates the importance of involving the family in the care of people living with HIV by educating them when they accompany their loved ones for clinic visits (Pius et al 2021 :6).…”
Section: Discussionsupporting
confidence: 85%
“…Perceived benefit is a concept of Pender Health Promotion Model that supports 6 major components of healthy lifestyle. These components include health responsibility, physical activity, nutrition, spiritual growth, interpersonal support and stress management (Eshah, Bond, & Sivarajan, 2010).The results of several studies supported that perceived benefits can improve health behavior in various areas (Kim, Ahn, & No, 2012;Lovell, Ansari, & Parker, 2010;Noroozi, Esmaili, Tahmasebi, & Vahdat, 2017;Salahshoori, Sharifirad, Hassanzadeh, & Mostafavi, 2014). In this study perceived benefits were associated with the prevention behavior of anemia during pregnancy.…”
Section: Discussionsupporting
confidence: 60%